Disentangling native and alien plant diversity in coastal sand dune ecosystems worldwide. (18th November 2020) - Tordoni, Enrico; Bacaro, Giovanni; Weigelt, Patrick; Cameletti, Michela; Janssen, John A.M.; Acosta, Alicia T.R.; Bagella, Simonetta; Filigheddu, Rossella; Bergmeier, Erwin; Buckley, Hannah L.; Ciccarelli, Daniela; Forey, Estelle; et al.
Abstract: Aims: (a) To disentangle the global patterns of native and alien plant diversity on coastal sand dune ecosystems across habitats and floristic kingdoms; (b) to determine the main drivers of variation in species richness in native and alien species in these endangered ecosystems; and (c) to test for an interaction between spatial scale and native–alien richness patterns, as predicted by the invasion paradox. Location: Global. Methods: We collated a dataset of 14, 841 vegetation plots in coastal sand dune ecosystems from around the world. Generalized Linear Models (GLMs) and Generalized Linear Mixed Models (GLMMs) were used to assess the patterns and main ecological determinants underlying native and alien species richness. Variation partitioning revealed the relative importance of environmental and anthropogenic variables. Results: GLMs revealed strong differences among both habitats and floristic kingdoms in the number of native and alien species. Specifically, native species richness increased along the sea–inland gradient and was higher in the Cape and Paleotropical kingdoms. In contrast, alien species richness was relatively similar across habitats and kingdoms, though some differences were detected. There were strong differences between the drivers of native and alien richness; anthropogenic factors such as gross domestic product were positively associated with alien richness whereas native richness was more strongly related to environmental factors. Furthermore, we found a weak support for an invasion paradox effect. Conclusions: Our results revealed the complexity of causal processes underpinning coastal sand dune plant biodiversity and highlight the importance of considering native and alien species separately. Recognizing these differences while researching variation in biodiversity patterns and processes at multiple spatial scales will lead to a better mechanistic understanding of the causes of invasion worldwide, and in coastal ecosystems in particular, allowing the development of more focused control and management measures. Abstract : We found strong differences in native and alien plant diversity and also in different habitats and floristic kingdoms in coastal dune ecosystems around the world. Our results provide only weak support for the invasion paradox hypothesis. Different drivers of species richness were identified for the two groups revealing the complexity of causal processes underpinning plant diversity in these environments.